2017
DOI: 10.1155/2017/9502067
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanism of Huannao Yicong Decoction Extract on the Ethology of Transgenic APP/PS1 Mice

Abstract: To investigate the mechanism of Huannao Yicong Decoction (HYD) extract on improving of learning memory of transgenic amyloid precursor protein (APP)/presenilin 1 (PS1) mice, we randomly divided 60 transgenic APP/PS1 mice of 3 months old into 4 groups: the model group, the Donepezil group, the HYD-L group, and the HYD-H group, with 15 C57BL/6J mice of the same genetic background as the control group. These mice were gavaged for 6 months in a row. The results showed that the latency was significantly shortened a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Interestingly, the levels of THSG, aloe emodin, emodin and physcion in HYD were signi cantly lower than those in the PMR and PMRP samples, indicating that the toxicity of the four components may be inhibited when combined. Using gas chromatography and mass spectrometry (GC-MS), we have found the main active components of HYD to include ferulic acid, stilbene glycoside, berberine hydrochloride, ginseng saponin Rg1, Rb1, Re, and emodin [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the levels of THSG, aloe emodin, emodin and physcion in HYD were signi cantly lower than those in the PMR and PMRP samples, indicating that the toxicity of the four components may be inhibited when combined. Using gas chromatography and mass spectrometry (GC-MS), we have found the main active components of HYD to include ferulic acid, stilbene glycoside, berberine hydrochloride, ginseng saponin Rg1, Rb1, Re, and emodin [20].…”
Section: Discussionmentioning
confidence: 99%
“…The pool was divided into four quadrants, and a platform was placed in the centre of the second quadrant. After the injection of clean water above the platform (1 cm), the water temperature was maintained at 23±2°C, and an appropriate amount of ink was added to hide the platform [20].…”
Section: Morris Water Maze Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Qi deficiency, blood stasis, and toxins can be respectively interpreted into modern concepts of aging symptoms, hyperlipemia, and Aβ and tau-protein deposition. Accumulating data have demonstrated that medicinal Chinese herbs or herbal formulas, such as Radix Ginseng , 14 , 15 Rhizoma Ligustici Chuanxiong , Rhizoma Coptidis , 16 , 17 Qifu Yin , 18 and Huannao Yicong Decoction, 19 22 tonify qi, dissolve blood stasis, and remove toxins to delay onset and progression of AD, and these have been widely used in clinics to treat AD in China.…”
Section: Introductionmentioning
confidence: 99%